The relation between cigarette price and hand-rolling tobacco consumption in the UK: an ecological study - Rothwell, Lucas; Britton, John; Bogdanovica, Ilze (BMJ Publishing Group, 2015)
OBJECTIVES: Cigarette price increases reduce smoking prevalence but as a tobacco control policy are undermined by the availability of lower cost alternatives such as hand-rolling tobacco. The aim of this descriptive study is to explore time trends in the price of manufactured cigarettes and hand-rolling tobacco, and in the numbers of people who smoke these products, over recent years in the UK. SETTINGS AND PARTICIPANTS: UK. OUTCOME MEASURES: Trends in the most popular price category (MPPC) data for cigarettes and hand-rolling tobacco from 1983 to 2012 adjusted for inflation using the Retail Price Index, and trends in smoking prevalence and the proportion of smokers using hand-rolling tobacco from 1974 to 2010. RESULTS: After adjustment for inflation, there was an increase in prices of manufactured cigarettes and hand-rolling tobacco between 1983 and 2012. Between 1974 and 2010, the prevalence of smoking fell from 45% to 20%, and the estimated total number of smokers from 25.3 to 12.4 million. However the number of people smoking hand-rolling tobacco increased from 1.4 to 3.2 million, and MPPC cigarette price was strongly correlated with number of people smoking hand-rolling tobacco. CONCLUSIONS: Although the ecological study design precludes conclusions on causality, the association between increases in manufactured cigarette price and the number of people smoking hand-rolling tobacco suggests that the lower cost of smoking hand-rolling tobacco encourages downtrading when cigarette prices rise. The magnitude of this association indicates that the lower cost of hand-rolling tobacco seriously undermines the use of price as a tobacco control measure.